Implementation of a web based low code programming interface for ROS2 operated robots - Pang, Yi Wei (Nanyang Technological University, 2023)
This project will investigate the result produced by integrating human factor into a simulation. Due to Covid-19, it enables us to realise the importance of HRC and how it can improve on factories productivity. Furthermore, with the recent development of technology such as VR, it enables us to enter a virtual environment and try out what it is like working in a factory. Through applications such as Unity, Oculus and ROS, it makes is possible to integrate them together and resulting in a simulation with human factor. This report aims to provide the process and steps taken to integrate Unity, Oculus and ROS together. Finally, conclusion and recommendation for future improvements and as well as reflection on learning outcome attained in the project will also be included.